2020
DOI: 10.1080/14686996.2020.1724824
|View full text |Cite
|
Sign up to set email alerts
|

Descriptors for dielectric constants of perovskite-type oxides by materials informatics with first-principles density functional theory

Abstract: Dielectric materials that can realize downsizing and higher performance in electric devices are in demand. Perovskite-type materials of the form ABO 3 are potential candidates. However, because of the numerous conceivable compositions of perovskite-type oxides, finding the best composition is technically difficult. To obtain a reasonable guideline for material design, we aim to clarify the relationship between the dielectric constants and other physical and chemical properties of perovskite-type oxides using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…[31][32][33] The modern calculation of dielectric constants is typically done using density functional perturbation theory (DFPT). 4,[34][35][36][37][38] Despite being a perturbation theory, DFPT can be calculated with a relatively low cost, and the results are less dependent on the exchange-correlation functional used, compared to properties such as bandgaps. 4 Therefore, many studies have involved analysis of datasets of dielectric constants aiming to understand trends or predict values for new materials.…”
Section: Data Driven Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] The modern calculation of dielectric constants is typically done using density functional perturbation theory (DFPT). 4,[34][35][36][37][38] Despite being a perturbation theory, DFPT can be calculated with a relatively low cost, and the results are less dependent on the exchange-correlation functional used, compared to properties such as bandgaps. 4 Therefore, many studies have involved analysis of datasets of dielectric constants aiming to understand trends or predict values for new materials.…”
Section: Data Driven Modelsmentioning
confidence: 99%
“…4,34 Some studies employ machine learning (ML) methods where a statistical model is trained. 35,36 For example, Umeda et al trained different ML models on a dataset of 3382 compounds. 35 They obtained good agreement with DFPT calculations; however, the reasons for this agreement are not discussed.…”
Section: Data Driven Modelsmentioning
confidence: 99%
“…Pilania et al [24] constructed prediction models of various material properties, including the dielectric constants, of one-dimensional chain structures. Noda et al [29] reported a model for perovskite-type oxides using partial least-squares regression. Related to these studies, Umeda et al [30] corrected the DFT calculation errors of the dielectric constants using ML, while Choudhary et al [31] proposed a classification model for exploration of materials with dielectric constants higher than 10.…”
Section: Introductionmentioning
confidence: 99%
“…Active learning is particularly appealing in scenarios where data is scarce and expensive to obtain. For energy materials design properties such as high-quality electronic structure [40], dielectric constants [22,[41][42][43], effective masses [44] and defect properties [45,46] are some high-profile examples where data-driven approaches are possible, but obtaining large sets of labelled data can be prohibitive to applying deep learning approaches. In these scenarios the availability of a method for reducing the number of samples required to train accurate, and reliable models is rather critical to the application of deep learning approaches in materials' science.…”
Section: Discussionmentioning
confidence: 99%